Cerebrolysin and Recovery After Stroke (CARS): A Randomized, Placebo-Controlled, Double-Blind, Multicenter Trial. Issue 1 (January 2016) - Muresanu, Dafin F.; Heiss, Wolf-Dieter; Hoemberg, Volker; Bajenaru, Ovidiu; Popescu, Cristian Dinu; Vester, Johannes C.; Rahlfs, Volker W.; Doppler, Edith; Meier, Dieter; Moessler, Herbert; Guekht, Alla
Abstract : Background and Purpose—: The aim of this trial was to investigate whether stroke patients who receive Cerebrolysin show improved motor function in the upper extremities at day 90 compared with patients who receive a placebo. Methods—: This study was a prospective, randomized, double-blind, placebo-controlled, multicenter, parallel-group study. Patients were treated with Cerebrolysin (30 mL/d) or a placebo (saline) once daily for 21 days, beginning at 24 to 72 hours after stroke onset. The patients also participated in a standardized rehabilitation program for 21 days that was initiated within 72 hours after stroke onset. The primary end point was the Action Research Arm Test score on day 90. Results—: The nonparametric effect size on the Action Research Arm Test score on day 90 indicated a large superiority of Cerebrolysin compared with the placebo (Mann–Whitney estimator, 0.71; 95% confidence interval, 0.63–0.79; P <0.0001). The multivariate effect size on global status, as assessed using 12 different outcome scales, indicated a small-to-medium superiority of Cerebrolysin (Mann–Whitney estimator, 0.62; 95% confidence interval, 0.58–0.65; P <0.0001). The rate of premature discontinuation was <5% (3.8%). Cerebrolysin was safe and well tolerated. Conclusions—: Cerebrolysin had a beneficial effect on function and global outcome in early rehabilitation patients after stroke. Its safety was comparable with that of the placebo, suggesting a favorable benefit/risk ratio. Because this study was exploratory and had a relatively small sample size, the results should be confirmed in a large-scale, randomized clinical trial. Clinical Trial Registration—: URL:http://www.clinicaltrialsregister.eu . Unique identifier: 2007-000870-21. Abstract : Supplemental Digital Content is available in the text.